CLIMATE CHANGE EFFECTS ON AQUATIC ECOSYSTEM: STRUCTURE AND DISEASE - Saurabh, Suman; Kumar, Prashant (The Scientific Temper, 2018)
Climate change is projected to cause significant alterations to aquatic biogeochemical processes, (including carbon dynamics), aquatic food web structure, dynamics and biodiversity, primary and secondary production; and, affect the range, distribution and habitat quality/quantity of aquatic. Nutrient and carbon enrichment will enhance nutrient cycling and productivity, and alter the generation and consumption of carbon-based trace gases. Consequently, the status of aquatic ecosystems as carbon sinks or sources is very likely to change. The magnitude, extent, and duration of the impacts and responses will be system and location-dependent